International relations of Asia - Shambaugh, David L. (Asia in world politics., 2014)
"As the world's most dynamic region, Asia embodies explosive economic growth, diverse political systems, vibrant societies, modernizing militaries, cutting-edge technologies, rich cultural traditions amid globalization, and strategic competition among major powers. As a result, international relations in Asia are evolving rapidly. In this fully updated and expanded volume, leading scholars from Asia, Europe, and North America offer the most current and definitive analysis available of Asia's regional relationships. They set developments in Asia in theoretical context, assess the role of leading external and regional powers, and consider the importance of subregional actors and linkages".